Hydraulic performance of new and used self-compensating micro-sprinklers - De Andrade, Stocler Manoel [UNESP]; Zanini, José Renato [UNESP]; Soares, Cristiana Araujo [UNESP] (Universidade Estadual de Londrina, 2015)
From the technical and economic perspectives, it is imperative that irrigation systems have extensive durability and high uniformity of application. The objective of this study was to compare the hydraulic performance of new and used (9 years of use with 4265 h of operation) self-compensating microsprinklers of the SuperNet LR model. The study was performed in a laboratory to evaluate flow in the range of pressure compensation, coefficient of manufacturing variation or discharge (CVF and CVQ), wetting pattern, distribution uniformity coefficient (DUC), and Christiansen uniformity coefficient (CUC).The new and used micro-sprinklers did not differ in CVF and CVQ, and were rated as excellent; they also did not differ in CUC or DUC. The coverage diameters of the new and used micro-sprinklers were the same as those given in the manufacturer's catalog. There were no significant differences in the flow rates of the new and used micro-sprinklers when subjected to the same pressure, but significant differences in flow rate were observed within the range of pressure compensation. When installed in an irrigation system, the useful life of micro-sprinklers can be considered to be greater than 9 years with 4265 h of operation.
Keywords: Localized irrigation; Micro-irrigation; Water distribution